0
$\begingroup$

I want to proove:

For points $P \neq Q \in \mathbb{R}$ and $a,b >0$ there is exactly one point $X \in [PQ]$ and exactly one point $X' \notin [PQ]$ with ratio $a:b$. For $a=b$ there is only one point $X \in [PQ]$ with $a:b$.

I know that $X$ divides $[PQ]$ in ratio $a:b$ if $$ \frac{d(X,P)}{d(X,Q)}=\frac a b$$ where $d(X,P)$ is the distance between $X$ and $P$.

My first thought was, that I take two points which has both the ratio $a:b$ and then show, that they are the same.

Any hints are welcome.

$\endgroup$
  • $\begingroup$ If the $x \in [P,Q]$ then $d(X,P) + d(X,Q) = |P-Q|$. Use that to show that if $d(X,P)/d(X,Q) = d(X',P)/d(X',Q)$ then $X=X'$. For $x \notin [P,Q]$, you instead have $|d(X,P) - d(X,Q)| = |P-Q|$. $\endgroup$ – fgp Apr 2 '14 at 11:23
  • $\begingroup$ I have to plug in $d(X,P) + d(X,Q) = |P-Q|$ for e.x. $d(X,P)$ or how should I start? $\endgroup$ – ulead86 Apr 2 '14 at 11:58
1
$\begingroup$

It can be thought as an analytic geometic solution.

Notice that line segmnet $[P,Q]$ can be parametrized by

$$\vec{f(t)}=\vec{P}+t(\vec{Q}-\vec P)$$ for $t\in [0,1]$ and $f(0)=P \ and \ f(1)=Q$

Set $X=f(t_0)$ and $k$ be the given ratio then

$$d(X,P)=|\vec f(t_0)-\vec f(0)|=t_0(\vec{|P-Q|})$$ and

$$d(X,Q)=|\vec f(t_0)-\vec f(1)|=(1-t_0)\vec{|P-Q|}$$

$$k=\dfrac{d(X,P)}{d(X,Q)}=\dfrac{t_0}{1-t_0}\implies t_0=\dfrac{k}{k+1}$$

If $t_0=1$ then write equation as $$ \dfrac 1 k=\dfrac{d(X,Q)}{d(X,P)}=\dfrac{1-t_0}{t_0}\implies t_0=\dfrac{k}{k+1}$$

You can easliy see that given ratio $k$ uniqly determine $t_0$ by above equation. So such a point is uniqe.

If $X\notin [P,Q]$ then $t_0>1$ in that case we will get similiar formula,

$$k=\dfrac{d(X,P)}{d(X,Q)}=\dfrac{t_0}{t_0-1}\implies t_0=\dfrac{k}{k-1}$$

which can be got in similiar way.

if $a=b$ i.e. $k=1$ it has no solution.

$\endgroup$
  • $\begingroup$ and how do I argue for $X \notin [PQ]$ and the 3rd case $a=b$? $\endgroup$ – ulead86 Apr 3 '14 at 7:49
0
$\begingroup$

I tried the following (using fgp's hint): $d(X,P)+d(X,Q)=d(P,Q)$

\begin{eqnarray} &&\frac{d(X,P)}{d(X,Q)} = \frac{d(X',P)}{d(X',Q)} \Leftrightarrow \frac{d(P,Q)-d(X,Q)}{d(X,Q)}=\frac{d(P,Q)-d(X',P)}{d(X',Q)} \\ &\Leftrightarrow & \frac{d(P,Q)}{d(X,Q)}-1=\frac{d(P,Q)}{d(X',Q)}-1 \Leftrightarrow \frac{d(P,Q)}{d(X,Q)}=\frac{d(P,Q)}{d(X',Q)} \\ &\Leftrightarrow &d(X',Q)=d(X,Q) \Rightarrow X=X' \end{eqnarray}

Is that ok too?

$\endgroup$
  • $\begingroup$ why not? it seems to be true. $\endgroup$ – mesel Apr 2 '14 at 15:45

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.